Open educational resources repositories literature review – Towards a comprehensive quality approaches framework. (October 2015) - Clements, Kati; Pawlowski, Jan; Manouselis, Nikos
Graphical abstract: Highlights: A comprehensive literature review on learning object repositories (LOR) quality approaches. Most cited quality approaches are "peer reviews" and "recommendation systems". User-generated, collaborative, quality instruments are favored for their sustainability. Main result is a Quality approach framework for LOR design. Abstract: Today, Open Educational Resources (OER) are commonly stored, used, adapted, remixed and shared within Learning object repositories (LORs) which have recently started expanding their design to support collaborative teaching and learning. As numbers of OER available freely keep on growing, many LORs struggle to find sustainable business models and get the users' attention. Previous studies have shown that Quality assurance of the LORs is a significant factor when predicting the success of the repository. Within the study, we analysed technology enhanced learning literature systematically regarding LORs' quality approaches and specific collaborative instruments. This paper's theoretical contribution is a comprehensive framework of LOR quality approaches (LORQAF) that demonstrates the wide spectrum of possible approaches taken and classifies them. The purpose of this study is to assist LOR developers in designing sustainable quality assurance approaches utilizing full the potential of collaborative quality assurance tools.